A New Model of a Vibro-impact Capsule Robot in the Gastric Digestive Liquid Environment - Hoang, Tien-Dat; Nguyen, Van-Du; Ngo, Quoc-Huy (Journal of Applied Nonlinear Dynamics, 2026)
Capsule robots (capsubot) are increasingly used in endoscopic operations, diagnostics, drug delivery, and the treatment of gastrointestinal diseases. In addition to meeting size requirements, the capsubot must be capable of controlling its movement within the digestive tract. This paper proposes a new model of a self-moving capsule device that exploits the vibro-impact effect, accounting for the influence of viscous resistance in the gastric digestive fluid environment. Adding the viscous resistance component $F_{D}$ will take into account the influence of factors such as liquid viscosity, density, liquid flow velocity and the size of capsule. The XPPAuto numerical simulation tool is used to determine the numerical solution for the mathematical model and evaluate the performance of the capsubot in gastric fluid. Numerical analysis results show that the impact gap (G), frequency (f), amplitude ($i_{0}$), and duty cycle (pulse width) of the stimulation signal significantly affect the capsubot's direction and displacement. These findings can be used to optimize control variables and design parameters, forming a foundation for building an experimental system to verify and evaluate the capsubot system's dynamic behavior. This approach also helps reduce time and costs in designing and manufacturing experimental models for developing active capsules.